Relasi Aktor dalam Perencanaan Pembangunan Desa Trembes Kecamatan Gunem Kabupaten Rembang - agus riyadi; Winda Qotrun Nada; Nur Hamid; Abdul Karim (Empower : Jurnal Pengembangan Masyarakat Islam, 2024)
Trembes Village, Gunem District, Rembang Regency has autonomy in managing its territory through development programs incorporated in Minister of Home Affairs Regulation (Permendagri) Number 114 of 2014. This research aims to understand the stages of village development planning and the relationships between actors in village fund-based implementation through musrenbang activities. In qualitative research with a case study approach, data is collected through observation, interviews, and documentation. The research results show that the development planning stages involve many actors and are documented in the village RPJM. Relations between actors have a dominant influence on the planning process. However, the final decision remains in the hands of the village head after going through the RT deliberation and village deliberation mechanisms.Â